Using Yield and Entropy-Based Characteristics for Circular Economy - Fred Compart; Martin Gräbner (Circular Economy and Sustainability, 2024)
Environmental impacts of the extant linear carbon economy and aspects of conservation of resources demand a transformation to a circular carbon economy (CCE). In view of this transformation, carbon-containing plastic products should be reused and recycled to prevent or minimize the release of their carbon content into the environment. Different plastic waste feedstock recycling strategies are applicable, with different degrees of feedstock destruction, depending on the degree of degradation and contamination of the intended recycle fractions. The evaluation of the effectiveness of recycling processes by substance and carbon-based yield and entropic characteristics could be a part of the overall evaluation strategy for recycling processes. Possible principles and base equations of such substance and carbon-based yield and entropic characteristics, extracted from the literature and adapted, are delineated in this article. Substance-based characteristics could be applied for physical recycling processes in which the aspired recovery substances remain preserved and are physically separated. A resort to carbon-based characteristics could be practiced for recycling and combustion processes, in which the feedstock is chemically destroyed, and new substances are possibly synthesized. Stylized process examples depict the way of a joint usage of yield and entropic characteristics.
Keywords: 330; Statistical entropy analysis; Circular economy; Circular carbon economy; Mechanical recycling; Chemical recycling